THE EVOLUTION OF AGRICULTURAL LAND AROUND THE SAND MINING AREA FROM 2011 – 2021 IN LELES DISTRICT, GARUT REGENCY, WEST JAVA - Astrid Damayanti; Helmi Rahmat Fachrizal; Kintan Maulidina (BRIN, 2024)
Mining activities can alter land use patterns, including converting agricultural land. The transformation of agricultural land is occurring at varying rates, whether rapid or gradual. The evolution of agricultural land may be observed in terms of its shape, area, and land function. This paper was prepared to determine the evolution of agricultural land due to the expansion of limestone mining in Leles District from 2011 to 2021 to support further research in this area. The data collection process employed a combination of historical Google Earth images, secondary data, and land farm surveys conducted in Leles District, Garut Regency, from 2011 to 2021. The images were then assessed to identify land shape, area, and function changes. Subsequently, the data were subjected to analysis and comparison with existing literature. The study results demonstrate the evolution of the site and the utilization of agricultural land as a consequence of mining development. The expansion of the mining area has resulted in the transformation of the surrounding land into agricultural land. During the observation period, the mining area increased by 98%, while the farming area decreased by 27%.